2022
DOI: 10.1111/cns.14014
|View full text |Cite
|
Sign up to set email alerts
|

The sound stimulation method and EEG change analysis for development of digital therapeutics that can stimulate the nervous system: Cortical activation and drug substitution potential

Abstract: Introduction The purpose of this study is to propose a treatment method and the effect on the nervous system of digital therapeutics, which is a new treatment method to replace surgery and drug prescription for the treatment and prevention of diseases. Methods The 20 subjects who participated in the experiment, including men and women, had an average age of 26 ± 2.40 years. The proposed treatment method used three types of sound stimulation and air or bone conduction sound transmission methods to induce total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Increased breathing stimulates baroreceptor reflexes present in the carotid arteries to produce RSA. Stimulation with this specific cycle affects the carotid artery and thus increases the RMSSD [58][59][60][61][62]. However, the aHRSR used in this study induced an increase in RMSSD when changing posture, but decreased the rate of change in HF of the participants.…”
Section: Discussion/conclusionmentioning
confidence: 61%
“…Increased breathing stimulates baroreceptor reflexes present in the carotid arteries to produce RSA. Stimulation with this specific cycle affects the carotid artery and thus increases the RMSSD [58][59][60][61][62]. However, the aHRSR used in this study induced an increase in RMSSD when changing posture, but decreased the rate of change in HF of the participants.…”
Section: Discussion/conclusionmentioning
confidence: 61%
“…Additionally, the action of falling off the bed at action index 15 also showed a similar increase in ANS. Among them, the vestibular system, which is related to falls, is judged to be the cause [ 38 , 39 ]. The vestibular system has the greatest correlation with falls and is connected to the cranial nerves, so it can affect the ANS and central nervous system at a faster rate [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, it is suggested that stimulation of aHRSR both improves the stability and homeostasis of the autonomic nervous system, and induces changes in the human body through additional physiological stimulation (Savabi et al, 2020 ; Skow et al, 2022 ; Swenne, 2013 ). This shows various possibilities for application, such as healthcare methods and biofeedback methods that individuals can use (Kim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%